Ewolucja pejzażu audiowizualnego we Francji - Ndiaye, Bara (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2005)
Television in France has been a significant element of public life. A majority of governments in the 4th and 5th Republics aimed to control audiovisual information. Television was present even before WWII, yet it could not develop. After the war its progress was inhibited by the long-term monopoly of the state. As the political forces were changing, so were the organizations controlling television. Due to the reforms of the 1980’s two sectors emerged in France: the state owned sector and the privately owned sector. At present the audiovisual landscape of France is made up of the public sector, incorporating French Television with channels F2 and F3, ARTE, TV5 and Canal France International, and a private sector with Canal Plus (Canal + since 1984), M6, La Cinquieme and TF1. Since its privatization of nearly twenty years ago, TF1 has been the leading channel.